Evaluating Creative Problem-Solving Test for Elementary Students: Evidence from Factor Analyses - Herianto; Rosnawati, Raden; Jusmiana, Andi; Mabanja, Ashiraf (Yayasan Pendidikan Dan Pengembangan Harapan Ananda, 2025)
The lack of reliable and valid instruments to assess creative problem-solving (CPS) in elementary students is a primary problem, especially within evolving educational frameworks. Purpose of this Research: This study aimed to examine the validity and reliability of a CPS assessment instrument focusing on the dimensions of originality, completeness, and practicality to develop a more accurate measurement model. Research Methods: Using a quantitative, cross-sectional design, the data were analyzed using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). Research Sample: Data were collected from a sample of 150 elementary school students in South Sulawesi Province, Indonesia. Results and Implications: The results indicated that the CPS instrument is best represented by two aspects: originality and completeness, while the practicality aspect was excluded. The implication of this finding is the provision of a refined, valid, and reliable two-factor CPS model. Impact: The impact is that educators now have a more robust tool to accurately measure student creativity, which supports the cultivation of 21st-century skills and informs curriculum development by focusing on empirically supported aspects of creative problem-solving.